How far can ion trap miniaturization go? Parameter scaling and space‐charge limits for very small cylindrical ion traps. (25th February 2014) - Tian, Yuan; Higgs, Jessica; Li, Ailin; Barney, Brandon; Austin, Daniel E.
<x xml:space="preserve">Abstract</x> A broad effort is underway to make radiofrequency (RF) ion trap mass spectrometers small enough for portable chemical analysis. A variety of trap geometries and fabrication approaches are under development from several research groups. A common issue is the reduced trapping capacity in smaller traps, with the associated reduction in sensitivity. This article explores the key variables that scale with trap size including RF voltage, frequency, electrical capacitance, power and pseudopotential well depth. High‐field electric breakdown constrains the maximum RF voltages used in smaller ion traps. Simulations show the effects of space charge and the limits of trapping capacity as a function of trap dimensions for cylindrical ion traps down to the micrometer level. RF amplitudes that scale as the1/3, 1/2 and 2/3 power of trap radius, r0, were studied. At a fixed level of performance, the number of analyzable ions scales as r0n, with n ranging from 1.55 to 1.75 depending on the choice of voltage scaling. The implications for miniaturized ion trap mass spectrometry are discussed. Copyright © 2014 John Wiley & Sons, Ltd.